Age-Related Differences in Alcohol Intake and Control Over Alcohol Seeking in Rats - Labots, Maaike; Cousijn, Janna; Jolink, Linda A.; Kenemans, J. Leon; Vanderschuren, Louk J. M. J.; Lesscher, Heidi M. B. (Frontiers in Psychiatry, 2018)
Alcohol use disorder (AUD) is characterized by excessive and persistent alcohol use, despite adverse consequences. AUD often originates during adolescence, as do other substance use disorders. However, despite periods of excessive alcohol intake, many adolescents reduce their alcohol use by early adulthood. Brain development, social context, personality traits, and genetic makeup are thought to play an important role in these age-dependent fluctuations in alcohol use. However, studies that directly investigate age-related differences in the effects of alcohol exposure on brain and behavior are sparse. Therefore, to better understand the relationship between adolescent alcohol consumption and AUD-like behavior, this study compared the degree of control over alcohol seeking in rats that differed in terms of age of onset of alcohol drinking and in their level of alcohol consumption. We hypothesized that control over alcohol seeking is more prominent in adolescent-onset rats than in adult-onset rats, and that control over alcohol seeking is related to the consumed amount of alcohol. To test this hypothesis, alcohol seeking in the presence of a conditioned aversive stimulus was assessed after 2 months of intermittent alcohol access (IAA) in rats that consumed alcohol from postnatal day 42 (adolescence) or day 77 (adulthood). The rats were subdivided into low (LD), medium (MD), or high (HD) alcohol drinking rats, in order to assess the impact of the extent of alcohol intake on control over alcohol seeking. The adolescent-onset animals consumed slightly, but significantly less alcohol compared to the adult-onset rats. In adult-onset rats, we found that conditioned suppression of alcohol seeking, i.e., reduction of alcohol seeking by presentation of a conditioned aversive stimulus, was most pronounced in LD. By contrast, in the adolescent-onset rats, MD and HD showed increased alcohol seeking compared to LD, which was suppressed by conditioned aversive stimuli. Taken together, these findings reveal a complex relationship between the age of onset and level of alcohol intake with control over alcohol seeking, whereby adolescent rats consume less alcohol than adults. In adult rats, control over alcohol seeking is negatively related to preceding levels of alcohol intake. By contrast, adolescent rats appear to retain control over alcohol seeking, even after a history of high levels of alcohol intake.